BASIL IONIC RESPONSES TO SEAWATER STRESS AND THE IDENTIFICATION OF GLAND SALT SECRETION - J. F. Ninga; L. H. Cuib; S. H. Yanga; S. Y. Aia; M.J. Lia; L. L. Suna; Y. Chena; R.H. Wanga; Z. B. Zenga (Journal of Animal and Plant Sciences, 2015)
Basil (Ocimum Basilicum) seedlings were subjected to 0,5%,10%,20% and 40% seawater for 10 days under shade house conditions. Increasing seawater concentration led to considerable reduction in plant dry matter accumulation. However, root growth was not affected till treated with 40% seawater. Accumulations of Na+ and Cl- were correlated with decline of Ca2+ and K+ in stems, roots or both. Contents of Ca2+ and K+ in leaves increased or remained relatively unchanged with increasing salt levels. In salinity-stressed plants, Na+ were partitioned mainly in roots and more than 50% of the K+ and Ca2+ were stored in leaves. Higher K+/Na+ and Ca2+/Na+ ratios in leaves rather than in roots and stems were observed in Basil plants. Scanning electron microscopy coupled with X-ray microanalysis showed that Basil leaf gland secretions contained Na+ and Ca2+. The Na+ secretion increased while Ca2+ secretion decreased with the increasing seawater concentration. These results suggested that Basil salt tolerance is associated with the compartmentation of Na+ in roots and the balance of K+, Na+ and Ca2+ in leaves as well as the salt secretion by the leaf glands.
Keywords: Ocimumbasilicum L.; Basil; Ion balance; Salt secretion; Seawater stress; X-ray microanalysis